A study on purchase intention towards AgroMas brand / Roemilia Baharin - Baharin, Roemilia (2015)
This paper is to examine purchase intention towards AgroMas brand. However, there not much study about the purchase intention towards AgroMas brand which mostly previous study is about SMEs product but they do not explained detail what brand they focusing on. Thus, the theoretical framework was done. With a simple random sampling method used in this research, about 80 questionnaires distributed to the consumers before the results have revealed relationship and significant of conceptual framework of this topic. The researcher distributed the questionnaires among the consumers that come to Giant Senawang during weekdays. There are three conceptual factors which are brand affect, brand familiarity, and brand attitude has been analysed. Then the result of the study would indicate the main influential purchase intention towards AgroMas brand.